Public Participation in Identifying Sendang Biru Spring Catchment in Karst Area of Southern Malang, Indonesia - Sahrina, Alfi; Masruroh, Heni; Rosyida, Fatiya; Wahyudi, Adip; Anggara, Arik; Ainul Labib, Mohammad; Khairul Naafi, Ahmad (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sendang Biru is a spring which located in Southern Malang karst area.This spring is utilized by the local people to fulfill their daily needs. The aim of this research is to determine the catchment area of Sendang Biru Spring by using public participation approach. The method used was public participation approach in research by identifying the problem and the condition. Furthermore, deciding the research spots that later will be checked. The results of the research is obtained by mapping the injection locations, namely Mbah Wajib Cave, Limbah Cave, and Swallow Hole. The injection was done in rainy season, in order to wait for the existence of water flow from the surface into the cave. It was done by the researcher along with the local people that usually make use of the spring. People and other related parties know that Sendang Biru has catchment area in Mbah Wajib Cave, and swallow hole. It can be seen visually that the solution poured/injected n these locations shows the connectivity with Sendang Biru Spring.